On the Occurrence of Neisosperma oppositifolia (Lamk.) Fosberg & Sachet at Kavaratti Island, Lakshadweep - Sivadas, P.; Narayanan, B.; Kumar, Muktesh (Indian Forester, 1987)
Neisosperma opposilifolia (Lamk.) Fosberg and Sachet is being reported here for the first time from Lakshadweep Island.